An Analysis of Profitability Determinants in China Banking Sector - Zhou, Zhe (2014)
During the period of 2006 to 2013, banking system in China has been through gradually significant reform and policy changes alongside with efficiency and resource allocation improvements. These could further improve profitability. Therefore, this study aims to investigate the profitability determinants of Chinese banking sector by selecting 38 banks located in the four most developed regions (Beijing, Shanghai, Guangzhou, Shenzhen) in China. Also, it classified the determinants into bank-specific indicators (asset size, asset quality, asset proportion, income-expenditure structure, capital adequacy, deposits, loans and employees productivity), and macro-economic indicators (economic activity, inflation, concentration and overall banking efficiency on industrial level) on the banks performance, which is measured by the return on total equity. The results in this study imply that ratios employed have different effects on the performance of banks in China.